Cadmium adsorption by biomass: comparison of solid pineapple waste, sugarcane bagasse and activated carbon /cSyaza Azhari - Syaza Azhari, 1990-; Rahmalan Ahamad, supervisor; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2011